Implications of geographical range changes and resultant sympatry for three Accipiter hawks on the Cape Peninsula, South Africa. (4th May 2019) - Little, Robin M; Navarro, Rene A
Abstract : Some invasive species are known to compete with and even displace indigenous species. Two Accipiter species historically indigenous to eastern South Africa have colonised the Cape Peninsula in the south-west of the country and have become sympatric with a third local Accipiter species. We investigated the changes in the occurrence reporting rates of all three species on the Cape Peninsula between 1982 and 2018 using data from the Atlas of the Birds of the Southwestern Cape and from the two data collection periods of the Southern African Bird Atlas Project (SABAP1 and 2). We found that the Black Sparrowhawk Accipiter melanoleucus has become more abundant and that the African Goshawk A. tachiro and the historically local Rufous-breasted Sparrowhawk A. rufiventris have declined since the invasion of the Cape Peninsula by Black Sparrowhawks, suggesting that the latter species has outcompeted and at least partially displaced the other two species. Although that may be the case, since the three species seem to have relatively stabilised population sizes after 2010 this could suggest progressive resource partitioning with a level of ecological isolation following the initial dominance interactions. Since the westward expansion of the ranges of the Black Sparrowhawk and the African Goshawk along the southern coastal region of South Africa were most likely facilitated by anthropogenic alteration of the landscape ultimately leading to the sympatry of the three species on the Cape Peninsula, we suggest that this is therefore a case of indirect human-caused alien invasion.